2021
DOI: 10.1097/iae.0000000000003026
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Risk Factors for Recurrence of Macular Edema Associated With Branch Retinal Vein Occlusion

Abstract: Purpose: To examine angiographic risk factors for the recurrence of macular edema associated with branch retinal vein occlusion.Methods: We consecutively included 51 patients with treatment-naive branch retinal vein occlusion involving the macular area. Each eye initially received 3 monthly ranibizumab injections, with additional injections as necessary. At Month 3, we examined parafoveal vessel diameter indexes (VDI) in all sectors using optical coherence tomography angiography and determined the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Supposing that deep capillaries drain interstitial fluid from the retina, ME more likely occurs in eyes without deep capillaries 21 . Moreover, capillary dilation and collateral vessel formation, which primarily occur in deep capillary plexus, are also observed in eyes with recurrent ME 14 , 15 . Our study did not assess these angiographic factors; nonetheless, we speculate that deep capillaries, which run between the INL and OPL 22 , possibly contribute to jagged border formation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Supposing that deep capillaries drain interstitial fluid from the retina, ME more likely occurs in eyes without deep capillaries 21 . Moreover, capillary dilation and collateral vessel formation, which primarily occur in deep capillary plexus, are also observed in eyes with recurrent ME 14 , 15 . Our study did not assess these angiographic factors; nonetheless, we speculate that deep capillaries, which run between the INL and OPL 22 , possibly contribute to jagged border formation.…”
Section: Discussionmentioning
confidence: 97%
“…We speculated that the jagged border formation is associated with retinal deep capillaries. Recent studies have reported on the mechanisms of persistent ME and have investigated potential predictors of frequent anti-VEGF injection in eyes with BRVO 10 15 , 21 . Deep capillary loss detected by OCTA may be associated with persistent ME 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RVO is associated with many risk factors for RVO, including age, the crossing of retinal arteries and veins (AV), high intraocular pressure, short eye axis, retinal vascular wall sclerosis, dyslipidemia, hyperglycemia, hypertension, smoking, etc. Its etiology is complex and the pathogenesis is not fully understood (3)(4)(5)(6). Currently, other than symptomatic treatments for RVO there is no fundamentally effective therapy available.…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography angiography visualizes retinal blood flow by extracting decorrelation signals that change among multiple OCT-B scans acquired at the same location; this facilitates detection of retinal nonperfusion, microaneurysms, and collateral vessels in eyes with RVO. [9][10][11][12][13] By contrast, it has also been reported that OCTA does not detect all of the lesions delineated by FA 14 ; this may be related to the association between the blood flow velocity and interscan time (IST) of OCTA. [15][16][17] If the blood flow velocity is below the detection threshold of the IST, it theoretically cannot be visualized by OCTA.…”
mentioning
confidence: 99%